2-Deoxy-D-Glucose Enhances Anesthetic Effects in Mice. (February 2015) - Wang, Hui; Xu, Zhipeng; Wu, Anshi; Dong, Yuanlin; Zhang, Yiying; Yue, Yun; Xie, Zhongcong
<x xml:space="preserve">Abstract</x> BACKGROUND: The mechanisms of general anesthesia by volatile drugs remain largely unknown. Mitochondrial dysfunction and reduction in energy levels have been suggested to be associated with general anesthesia status. 2-Deoxy-D-glucose (2-DG), an analog of glucose, inhibits hexokinase and reduces cellular levels of adenosine triphosphate (ATP). 3-Nitropropionic acid is another compound which can deplete ATP levels. In contrast, idebenone and L-carnitine could rescue deficits of energy. We therefore sought to determine whether 2-DG and/or 3-nitropropionic acid can enhance the anesthetic effects of isoflurane, and whether idebenone and L-carnitine can reverse the actions of 2-DG. METHODS: C57BL/6J mice (8 months old) received different concentrations of isoflurane with and without the treatments of 2-DG, 3-nitropropionic acid, idebenone, and L-carnitine. Isoflurane-induced loss of righting reflex (LORR) was determined in the mice. ATP levels in H4 human neuroglioma cells were assessed after these treatments. Finally, 31P-magnetic resonance spectroscopy was used to determine the effects of isoflurane on brain ATP levels in the mice. RESULTS: 2-DG enhanced isoflurane-induced LORR (P = 0.002, N = 15). 3-Nitropropionic acid also enhanced the anesthetic effects of isoflurane (P = 0.005, N = 15). Idebenone (idebenone + saline versus idebenone + 2-DG: P = 0.165, N = 15), but not L-carnitine (L-carnitine + saline versus L-carnitine + 2-DG: P < 0.0001, N = 15), inhibited the effects of 2-DG on enhancing isoflurane-induced LORR in the mice, as evidenced by 2-DG not enhancing isoflurane-induced LORR in the mice pretreated with idebenone. Idebenone (idebenone + saline versus idebenone + 2-DG: P = 0.177, N = 6), but not L-carnitine (L-carnitine + saline versus L-carnitine + 2-DG: P = 0.029, N = 6), also mitigated the effects of 2-DG on reducing ATP levels in cells, as evidenced by 2-DG not decreasing ATP levels in the cells pretreated with idebenone. Finally, isoflurane decreased ATP levels in both cultured cells and mouse brains (β-ATP: P = 0.003, N = 10; β-ATP/phosphocreatine: P = 0.006, N = 10; β-ATP/inorganic phosphate: P = 0.001, N = 10). CONCLUSIONS: These results from our pilot studies have established a system and generated a hypothesis that 2-DG enhances anesthetic effects via reducing energy levels. These findings should promote further studies to investigate anesthesia mechanisms.